Lived experience of people with adrenocortical carcinoma and associated adrenal insufficiency. Issue 4 (6th June 2022) - Yeoh, Phillip; Czuber‐Dochan, Wladyslawa; Aylwin, Simon; Sturt, Jackie
Abstract: Introduction: Adrenocortical carcinoma (ACC) is a rare cancer with an annual incidence of 0.7–2 cases per million population and 5‐year survival of 31.2%. Adrenal insufficiency (AI) is a common and life shortening complication of ACC, and little is understood about how it impacts on patients' experience. Objective: To understand patients' lived experience of the condition, its treatment, care process, impact of AI on ACC wellbeing, self‐care needs and support. Methods: Systematic review of MEDLINE, EMBASES, CINAHL, PsycINFO and Open Grey for studies published until February 2021. All research designs were included. The findings underwent a thematic analysis and narrative synthesis. Studies quality was assessed using mixed method assessment tools. Results: A total of 2837 citations were identified; 15 titles with cohort, cross‐sectional, case series and case report study designs met the inclusion criteria involving 479 participants with adrenal insufficiency secondary to adrenocortical carcinoma (AI/ACC). Quantitative research identified impacts of disease and treatment on survivorship, the burden of living with AI/ACC, toxicity of therapies, supporting self‐care and AI management. These impact factors included adjuvant therapies involved and their toxicities, caregivers/family supports, healthcare and structure support in place, specialist skill and knowledge provided by healthcare professional on ACC management. No qualitative patient experiences evidence was identified. Conclusion: ACC appears to have high impact on patients' wellbeing including the challenges with self‐care and managing AI. Evidence is needed to understand patient experience from a qualitative perspective. Abstract : ACC appears to have high impact on lived experience of patients including their wellbeing and AI management. Further qualitative study is needed to understand the interactions of these two conditions, it's influences on patients' journey and survivorship.